The Effectiveness of Skincare Laws and Regulations Can Jeopardize the Condition of the Human Body - Jayady, Try (Manunggal Halim Jaya, 2025)
Determining the legal framework and liability of skincare manufacturers for skin health is a critical issue. Normative legal research examines the structure, foundation, and components of the regulatory system, providing shape and boundaries to its application. Deviant behaviors, such as crimes, continue to exist in society. The application of law as a means to address these issues is expected to yield appropriate and effective solutions. The form and nature of criminal offenses or violations should reflect fairness and appropriateness in their resolution.